Nitrogen starvation or glucose limitation induces conidiation in constantly shaken liquid cultures of Neurospora crassa. - B. T. Müller; V. E.A. Russo (Fungal Genetics Reports, 1989)
Nitrogen starvation or glucose limitation induces conidiation in constantly shaken liquid cultures of Neurospora crassa.